Strategi Pengembangan BUMDes Melalui Pemanfaatan Sumber Daya Alam, Perkebunan Durian untuk Meningkatkan Pendapatan Desa - Mentari Mentari; Gusneli Gusneli; Amrizal Amrizal (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
This study aims to formulate strategies for developing Village-Owned Enterprises (BUMDes) through the utilization of natural resources in the durian plantation sector in Dahai Village, Paringin District, Balangan Regency. The research employed a qualitative approach with a case study design, involving village officials, BUMDes managers, village facilitators, and community members as informants. Data were collected through in-depth interviews, observation, and document analysis, and then analyzed thematically using descriptive methods. The findings indicate that BUMDes Dahai Maju Berkarya holds strategic potential in developing durian plantations, with positive feasibility projections in market, technical, managerial, and financial aspects. Furthermore, the mentoring process improved human resource capacity and community participation, although challenges remain in terms of capital, technical expertise, and digital marketing needs. The study concludes that durian plantation development through BUMDes is feasible and can enhance community welfare while strengthening local economic independence. Practical implications highlight the need for financial support and external partnerships, while theoretical contributions enrich the literature on village development based on local potential with a focus on specific commodities.